2005
DOI: 10.2174/092986705774933407
|View full text |Cite
|
Sign up to set email alerts
|

Development of Lymphatic Vessels: Tumour Lymphangiogenesis and Lymphatic Invasion

Abstract: In human solid cancer, the lymph node status is the most important prognostic indicator for the clinical outcome of patients. Follow-up data has shown that about 80% of metastasis follows an orderly pattern of progression via the lymphatic network while about 20% systemic metastasis occurs, bypassing the lymphatic system. Over the past few years, advances have been made in understanding the cellular and molecular aspects of physiological lymphangiogenesis and tumour-induced lymphangiogenesis, and the majority … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 97 publications
(129 reference statements)
1
18
0
4
Order By: Relevance
“…Genes that are dysregulated in lymphangiomas are unknown, and only very recently we have provided evidence for up-regulation of VEGFR-2 and -3 in lymphangioma LECs (Norgall et al, 2007). Due to recent advantages in lymphangiogenesis research (Wilting et al, 2005), it can be expected that our understanding of the molecular mechanisms involved in normal and aberrant development of lymphatics will increase rapidly. In order to test the effectiveness of new therapeutics in vivo, animal models for lymphangiomas are needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genes that are dysregulated in lymphangiomas are unknown, and only very recently we have provided evidence for up-regulation of VEGFR-2 and -3 in lymphangioma LECs (Norgall et al, 2007). Due to recent advantages in lymphangiogenesis research (Wilting et al, 2005), it can be expected that our understanding of the molecular mechanisms involved in normal and aberrant development of lymphatics will increase rapidly. In order to test the effectiveness of new therapeutics in vivo, animal models for lymphangiomas are needed.…”
Section: Discussionmentioning
confidence: 99%
“…3B), whereas LECs generally appeared to be MMP2-negative. It has been shown that Vascular Endothelial Growth Factor-C and -D (VEGF-C/-D) are critical regulators of embryonic and tumor-induced lymphangiogenesis (Wilting et al, 2005). Human VEGF-C and -D bind VEGF receptors (R)-2 (KDR) and -3 (Flt-4) with high affinity.…”
Section: Human Lymphangiomamentioning
confidence: 99%
“…The cells, which can intravasate into the preexisting or tumor-induced neoangiogenic blood or lymphatic vessels, can form metastases in draining lymph nodes (LN) and at distant sites. Because of differences in the endothelial and vessel wall structure, lymphatic vessels likely offer pathways of lower resistance for migrating cells, which is associated with the fact that approximately 80% of metastasizing tumors preferentially spread via the lymphatic system (2).…”
Section: Introductionmentioning
confidence: 99%
“…The impairment of these functions leads to lymphoedema and disturbances in immune responses (Oliver and Alitalo 2005;Randolph et al 2005;Zawieja 2005). Lymphatic vessels are the main routes for the intravasation and dissemination of cancer cells, with lymph node metastasis being a prognostic factor for the clinical outcome in human carcinomas (Cao 2005;Oliver and Alitalo 2005;Wilting et al 2005).…”
mentioning
confidence: 99%